Parental Psychological Control and Adolescent Aggressive Behavior: Deviant Peer Affiliation as a Mediator and School Connectedness as a Moderator - Tian, Yunlong; Yu, Chengfu; Lin, Shuang; Lu, Junming; Liu, Yi; Zhang, Wei (Frontiers in Psychology, 2019)
Abundant evidence has demonstrated an association between parental psychological control and adolescent aggressive behavior. However, the mediating and moderating mechanisms underlying this relation are still under-investigated. Grounded in the social development model and stress-buffering model, this study investigated whether deviant peer affiliation mediates the relation between parental psychological control and adolescent aggressive behavior, and whether this indirect link is moderated by school connectedness. A total of 4265 adolescents (Meanage = 13.66 years, SD = 2.74, 48.63% male) from southern China completed questionnaires regarding parental psychological control, deviant peer affiliation, school connectedness, and aggressive behavior. Structural equation models revealed that the relation between parental psychological control and aggressive behavior is partially mediated by deviant peer affiliation. Moreover, this indirect link was stronger for adolescents with low levels of school connectedness than for those with high levels of school connectedness. This study thus identifies the potential underlying mechanism by which parental psychological control is associated with adolescent aggressive behaviors, which has important implications for theory and prevention.